METHODOLOGY OF SELECTION OF EFFICIENT MOVING STRUCTURE FOR TRANSPORTATION OF FAST DESTRUCTIVE LOADS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Successful storage of perishable goods can only be achieved by maintaining a special temperature regime that is necessary to maintain quality at all stages of the product life cycle from production to consumption (including transportation).The main criterion in the selection of rolling stock for the transport of perishable goods is to ensure the safety of the cargo. To do this, take into account the nature of the route, the number of unloading points on the distribution route, the type of cooling device of the car-refrigerator.This paper is based on the basic steps of an effective rolling stock selection methodology for transporting perishable goods.